HARMONY MASJID AGUNG KRATON SURAKARTA HADININGRAT - Purwadi Purwadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2014)
This article will describe about spiritual, cultural and social activity in Masjid Agung Kraton Surakarta Hadiningrat. There are Grebeg Besar, Grebeg Pasa, Grebeg Mulud and Malem Selikuran ceremony. The Javanese community always do religiocity ritual that aim to get peace and harmony. Islam teaching able and Javanese culture value more together. Local identity become tool dakwah Islamiyah. Multiculturalism and tolerance spirit give enlightmen to environment. Traditional wisdom can be seeked in the big mosque of Kraton Surakarta that become central religious activity. Everyone should study traditional wisdom as symbolized in herritage of Masjid Agung Kraton Surakarta. Thereare much teaching that can be used as nation character building in global era.